Synthetic Diagnostic for Interpreting the ECE Spectrum on EAST. (18th August 2018) - Zhou, Tianfu; Liu, Yong; Ti, Ang; Figini, Lorenzo; Zhao, Hailin; Zhu, Zeying; Ling, Bili
Abstract: The current-drive technique, using lower hybrid waves (LHWs) for radio-frequency heating, is of highest priority on EAST, and over 100 s steady-state long-pulse H-mode plasmas have been achieved recently. The suprathermal electrons driven by LHWs make the interpretation of electron cyclotron emission (ECE) spectrum complex. This paper presents the preliminary results of a synthetic diagnostic for interpreting the ECE measurement results in both ohmic and LHW-heated plasmas on EAST. The synthetic diagnostic is realized by using the simulation code SPECE. The agreement between the simulations and experimental results is fairly good for the ohmic cases. For the LHW case, the simulations don't agree well enough with the measurements.